Facile Synthesis, Analysis of Physico-Chemical Properties and Tape Casting of Al2O3 Nanoparticles - Segar Deepi, Alagu; Dharani Priya, Srinivasan; Edwardraj Freeda Christy, Clementz; Samson Nesaraj, Arputharaj (Asian Journal of Chemistry, 2022)
Alumina (Al2O3) powder was synthesized by simple wet-chemical precipitation method. The phase study was done using XRD confirming the FCC phase. FTIR showed the presence of Al-O vibrations. Particle size analysis (PSA) confirmed the presence of particles in the range of 300 nm. The EDX confirmed the presence of Al and O elements in the samples only and no impurity elements. SEM exhibited the ultrafine nature of the particles. The tape casting of Al2O3 nanoparticles was carried out with suitable organic ingredients. Based on the trials, the best composition for alumina tape casting was optimized. The SEM of green alumina thin sheet resulted in good surface behaviour. Optimized composition may be used for fabricating thin Al2O3 based electrical components for application in electronics industry.